Tuberculous lymphadenitis in children: A systematic review of case reports - García Rodríguez, Tatiana Lizseth (2022)
Objective: To conduct a systematic review of tuberculous lymphadenitis cases in children published until April 2022. Material and methods: Case reports of tuberculous lymphadenitis by M. tuberculosis in children were searched in Scopus, PubMed, Science Direct, Web of Science, LILACs, Ovid MEDLINE, EBSCO, and BMC Case Reports databases. Results: Forty-one reports were selected and a total of 46 patients were included. The majority were males (52,2%) of 8,5 (5-12) years old. The time of disease was 2 (1-5) months. The most frequent clinical manifestations were palpable lymphadenopathy (60,9%), fever (52,2%) and cough (26,1%). Weight loss (17,4%), scrofula (15,2%), respiratory distress (13%), hyporexia (13%), localized pain (13%), skin rash (13%), night sweats (4.3%), abdominal pain (4.3%) and jaundice (2,2%) were also founded. Cervical nodes were most frequently involved (71,4%). Only 17,4% were associated with lung involvement. PPD was positive in 77.1%, bacilloscopy in 17.2%, histopathology in 94,1% and culture in 58,8%. Conclusions: Tuberculous lymphadenitis in children was more frequent in boys, between 5 and 12 years, immunized by BCG and without known contact with tuberculosis. The principal symptoms were palpable lymphadenopathy, fever and cough. However, atypical symptoms were respiratory difficulty, localized pain, skin rash, abdominal pain, and jaundice. Cervical nodes were the most affected. The test with greatest sensitivity was the histopathological study which detected 94,1% of cases.